A QUALITATIVE ANALYSIS OF PUBLIC PERCEPTION OF WORK ETHICS IN NIGERIA’S PUBLIC SECTOR - Oloyede Raheem, Lawal; AFOLAYAN, Michael Ayorinde (Annals of Spiru Haret University. Economic Series, 2023)
The Nigerian public service is crucial to the country’s economic development. This is because a vibrant public service sector is able to harness effectively overhead taxes and also account for public expenditure at all levels. The objective of this study is to investigate how public servants perceive work ethics to positively influence organization success and productivity in Nigeria public sector. In this study, researcher used qualitative to analyse the response of 15 individuals from the public who have visited a typical public office at least 3 times within the last one years. An interview form containing 7 items was administered, and the results was analyzed from themes that give true picture of the perception of respondents. It was observed that worker in public service are not professional enough, taking their jobs with levity. As a result, this study recommends publics service reforms.